2009
DOI: 10.1021/je900648p
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Properties of Ionic Liquids and IoNanofluids of Imidazolium and Pyrrolidinium Liquids

Abstract: Complex systems based on nanomaterials and common solvents have been shown to have thermophysical properties that can revolutionize current utilization of heat transfer fluids and heat storage cycles. This has been made possible by the existence of thermal conductivity enhancements derived from the presence of additional mechanisms of heat transfer in comparison with the base solvent. Ionic liquids have been shown to have thermophysical properties that justify the replacement of several of the chemical process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
174
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 228 publications
(190 citation statements)
references
References 46 publications
15
174
0
1
Order By: Relevance
“…Results from our studies [7][8]36] showed that ionanofluids containing MWCNT exhibit enhanced thermal conductivity and specific heat capacity compared to their base ionic liquids, a fact confirmed by [42].These properties further increase with concentration of nanoparticles and fluid temperature in some extend. Other attractive features of ionanofluids are that they are designable and fine-tuneable through their base ionic liquids for desired properties and tasks.…”
Section: Ionanofluidssupporting
confidence: 59%
See 2 more Smart Citations
“…Results from our studies [7][8]36] showed that ionanofluids containing MWCNT exhibit enhanced thermal conductivity and specific heat capacity compared to their base ionic liquids, a fact confirmed by [42].These properties further increase with concentration of nanoparticles and fluid temperature in some extend. Other attractive features of ionanofluids are that they are designable and fine-tuneable through their base ionic liquids for desired properties and tasks.…”
Section: Ionanofluidssupporting
confidence: 59%
“…Recent studies of this group [7][8] showed that ionanofluids containing multi-walled carbon nanotubes (MWCNT) exhibit significantly higher thermal conductivity and specific heat capacity compared to their base ionic liquids and they further increase with temperature and loading of MWCNT.…”
Section: Figure 1 Annual Publications On Nanofluidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, DBSA-PANI nanoparticles acted as surfactant and dopant [3]. DBSA modified the surface of nanoparticles and improved the stability of nanofluids [2,7] while water played as another hydrogen bond donor in this case [10,18]. Interaction of dopants and DES ions was also revealed to contribute to enhancement in thermal conductivity of DES based nanofluids.…”
Section: Resultsmentioning
confidence: 77%
“…The term of ionanofluid was defined as dispersion containing nanomaterials and ionic liquids [10]. Ionic liquids are advanced due to their high density, good heat capacity, good thermal and chemical stability and low vapor pressure [13].…”
Section: Introductionmentioning
confidence: 99%